Deconstructing Desire: Sexism and Power in Maroon 5's Animals - Sanjaya, Firman Hadi; Samanik, Samanik; Maretha, Carla (Universitas Tanjungpura, 2025)
This study employs a qualitative content analysis to examine Maroon 5's